Survei Perilaku Merokok pada Mahasiswa Program Studi Promosi Kesehatan Politeknik Negeri Jember : Smoking Behavior Survey Among Students of the Health Promotion Study Program at the State Polytechnic of Jember - Nurina Aprilya; Puspitasari, Nilam; Abdul Rauf, Muhammad; Abdi Suandana, Iwan; Fathur Rachman, Rizaldy (Journal of Public Health Education, 2025)
Introduction: Smoking behavior among adolescents and young adults remains a serious health issue, including within academic environments. Objectives: This study aims to determine the prevalence and characteristics of smoking behavior among students of the Health Promotion study program at the State Polytechnic of Jember. Method: This research used a descriptive quantitative method with a total sample of 25 male students from the 2022, 2023, and 2024 cohorts, selected through total sampling. Data were collected using a questionnaire and analyzed descriptively. Result: The results showed that 48% of respondents engaged in smoking behavior, with the majority consuming 1–5 cigarettes per day. Most respondents were aged between 19–21 years, a vulnerable phase influenced by social pressure and environmental factors. Conclution: Despite having a background in health education, there is a gap between the students' knowledge and their smoking behavior. Factors such as peer pressure, academic stress, and media influence are the main triggers of smoking habits. These findings highlight the need for more serious efforts to control smoking behavior among students, especially health students who are expected to be role models in promoting a healthy lifestyle.